Bipedicled transverse abdominal flap for coverage of exposed iliac crest due to post traumatic tissue loss in left inguinal region - Naik, Narendra G.; Karandikar, Sangram (International Journal of Research in Medical Sciences, 2016)
It is a surgical challenge for any plastic surgeon to choose the type of flap in the case of large inguinal canal tissue loss with exposed crest of ilium. Most repair methods provide inadequate closure of the defect for the large tissue loss over the inguinal region with exposure of the iliac crest. There are very few cases reported in the literature about transverse bipedicled abdominal flap for tissue defect over the inguinal region with exposure of the iliac crest bone and upper part of the thigh. In this case, by taking advantage of the large, loose, and lax nature of the abdominal skin, systematic primary closure of the donor as well as recipient site has been successfully achieved.